Development of training guide johari windows in improving student self-disclosure - Fatma Nofriza (Indonesian Counselor Association (IKI), 2017)
Persons with disabilities is a condition of physical disability of the individual as a normal human being. Various problems occur in persons with disabilities in social institutions such as the Balai Besar Rehabilitasi Vokasional Bina Daksa (BBRVBD) able to communicate openly with its environment. Johari windows is one technique to alleviate the problems of individual self-disclosure. The purpose of this study is to improve the skills of beneficiaries to be able to communicate who think, feel good about themselves and about others who frequently interact with it as it is and with the right language. This study uses research and development. The model used is a model development research and development (R&D). The results indicate that the development of this product has a usability criteria, eligibility, accuracy, the attractiveness and appropriate when used for student beneficiaries BBRVBD.